2011
DOI: 10.1186/1471-2458-11-887
|View full text |Cite
|
Sign up to set email alerts
|

The influence of population characteristics on variation in general practice based morbidity estimations

Abstract: Background: General practice based registration networks (GPRNs) provide information on morbidity rates in the population. Morbidity rate estimates from different GPRNs, however, reveal considerable, unexplained differences. We studied the range and variation in morbidity estimates, as well as the extent to which the differences in morbidity rates between general practices and networks change if socio-demographic characteristics of the listed patient populations are taken into account. Methods: The variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…We did not adjust for other characteristics of the populations, such as socioeconomic status, ethnicity, and degree of urbanization. In an earlier study, we already showed that these characteristics did not explain any of the variance between networks [3]. The same was found for differences between GPs and general practices.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…We did not adjust for other characteristics of the populations, such as socioeconomic status, ethnicity, and degree of urbanization. In an earlier study, we already showed that these characteristics did not explain any of the variance between networks [3]. The same was found for differences between GPs and general practices.…”
Section: Discussionmentioning
confidence: 50%
“…We and others [3, 4] looked at differences between registration network within the same country and found large differences that could not be fully explained. When comparing registration-based data between countries, we expected similar differences in the organization of data collection as between networks in the Netherlands.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[29] The differences between the cohorts in Amsterdam and Eindhoven may partly be explained by methodological differences (the shorter existence of SMILE (fewer active problems) and coding agreements (fewer MUS, but more psychological codes in SMILE)), different populations of general practitioners (shorter experience in coding problems in SMILE) and patient factors (more stable population; more females in SMILE). However, socio-demographic characteristics of populations cannot explain the differences in morbidity estimations among these cohorts [30].…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of osteoarthritis, for example, ranges from 10 to 60 per 1000 person years between GPRNs. Overall, prevalence figures estimated from GPRNs show more variation than incidence Figures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%